A New Point Mutation (P157S) in the Reverse Transcriptase of Human Immunodeficiency Virus Type 1 Confers Low-Level Resistance to (−)-β-2′,3′-Dideoxy-3′-Thiacytidine - Smith, Robert A. (American Society for Microbiology, 1999)
A P157S mutation in the reverse transcriptase (RT) of human immunodeficiency virus type 1 conferred fivefold resistance to (−)-β-2′,3′-dideoxy-3′-thiacytidine in cell culture. Interestingly, the P157S mutation resulted in increased sensitivity (two- to threefold) to 3′-azido-3′-deoxythymidine (AZT) and to (R)-9-(2-phosphonylmethoxypropyl)adenine (PMPA). A similar increase in susceptibility to AZT and to PMPA was also conferred by the M184V mutation in RT.